Examen Especial a Propiedad, Planta y Equipo de Unidad Educativa Pilco Correa y Cía. San Gerardo Loja, periodo 01 enero-31 diciembre 2022 - Alvarado Armijos, Yadira Fernanda (2024)
This research entitled Special Examination of Property, Plant, and Equipment of Unidad Educativa Pilco Correa y Cia. San Gerardo Loja, period January 1 – December 31 2022, has been developed in accordance with the Academic Regime Regulations of Universidad Nacional de Loja as a requirement to obtain the degree in Accounting and Auditing. The purpose is to contribute to the decision-making process of Unidad Educativa Pilco Correa y Cia. San Gerardo. In order to achieve the stated objectives, the phases of the Special Examination were carried out. The process began with the Planning phase, in which preliminary knowledge of Unidad Educativa Pilco Correa y Cia. San Gerardo Loja was obtained through a prior visit with the purpose of colleting timely information. This allowed the identification of deficiencies and the preparation of the Risk Assessment and Rating Matrix. The application of substantive and compliance tests, detailed in the respective audit programs was determined. An internal control evaluation was conducted on the Property, Plant and Equipment account to determine the reasonableness of the balances presented in the financial statements, resulting in a moderate level of risk and moderate confidence. Significant findings were documented in narrative sheets, analyzed, and verified, ensuring compliance with current regulations and Generally Accepted Accounting Principles with the respective evidence. Among the main findings were the lack of a manual for policies and procedures for the acquisition of Property, Plant and Equipment, absence of periodic physical verification, presence of assets in a state of deterioration or obsolescence, and assets that have exceeded their useful life. In response to there weaknesses, comments, conclusions, and recommendations were proposed and presented in the Audit Report as alternatives for improving the management, custody and control of Property, Plant and Equipment. These suggestions are intended to enhance the development of operations and the correct application of internal control within the institution to achieve its objectives.